Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

derive f=GMm/r^2 derive f=G Mm/r^2. derive f=GMm/r^2 derive f=GMm/r^2 derive f=GMm/r^2 derive f=GMm/r^2 derive f=GMm/r^2 derive f=GMm/r^2 derive f=GMm/r^2

derive f=GMm/r^2
derive f=GMm/r^2.
derive f=GMm/r^2
derive f=GMm/r^2
derive f=GMm/r^2
derive f=GMm/r^2
derive f=GMm/r^2
derive f=GMm/r^2
derive f=GMm/r^2

Grade:9

1 Answers

Arun
25763 Points
3 years ago
Mathematicians and astronomers figured this out about the time of Newton. It seems that this law was deduced by looking at the orbits of planets, which were stable and elliptical. There is some controversy as to who understood this first, but it seems Newton may have done the most with it, showing that the attraction to a sphere would be the same as if all its mass were concentrated at the center, and describing the paths of orbiting objects. 
 

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free